Recent Advances in Bioactive Flavonoid Hybrids Linked by 1,2,3-Triazole Ring Obtained by Click Chemistry - Daniela Pereira; Madalena Pinto; Marta Correia-da-Silva; Honorina Cidade (Molecules, 2021)
As a result of the biological activities of natural flavonoids, several synthetic strategies aiming to obtain analogues with improved potency and/or pharmacokinetic profile have been developed. Since the triazole ring has been associated with several biological activities and metabolic stability, hybridization with a 1,2,3-triazole ring has been increasingly reported over the last years. The feasible synthesis through copper (I) catalyzed azide-alkyne cycloaddition (CuAAC) has allowed the accomplishment of several hybrids. Since 2017, almost 700 flavonoid hybrids conjugated with 1,2,3-triazole, including chalcones, flavones, flavanones and flavonols, among others, with antitumor, antimicrobial, antidiabetic, neuroprotective, anti-inflammatory, antioxidant, and antifouling activity have been reported. This review compiles the biological activities recently described for these hybrids, highlighting the mechanism of action and structure–activity relationship (SAR) studies.